Economic assessment of patient navigation to colonoscopy‐based colorectal cancer screening in the real‐world setting at the University of Chicago Medical Center. Issue 21 (25th October 2018) - Kim, Karen E.; Randal, Fornessa; Johnson, Matt; Quinn, Michael; Maene, Chieko; Hoover, Sonja; Richmond‐Reese, Valerie; K. L. Tangka, Florence; Joseph, Djenaba A.; Subramanian, Sujha
Abstract : Background: This report details the cost effectiveness of a non‐nurse patient navigation (PN) program that was implemented at the University of Chicago Medical Center to increase colonoscopy‐based colorectal cancer (CRC) screening. Methods: The authors investigated the impact of the PN intervention by collecting process measures. Individuals who received navigation were compared with a historic cohort of non‐navigated patients. In addition, a previously validated data‐collection instrument was tailored and used to collect all costs related to developing, implementing, and administering the program; and the incremental cost per patient successfully navigated (the cost of the intervention divided by the change in the number who complete screening) was calculated. Results: The screening colonoscopy completion rate was 85.1% among those who were selected to receive PN compared with 74.3% when no navigation was implemented. With navigation, the proportion of no‐shows was 8.2% compared with 15.4% of a historic cohort of non‐navigated patients. Because the perceived risk of noncompletion was greater among those who received PN (previous no‐show or cancellation, poor bowel preparation) than that in the historic cohort, a scenario analysis was performed. Assuming no‐show rates between 0% and 50% and using a navigated rate of 85%, the total incremental program cost per patient successfully navigated ranged from $148 to $359, whereas the incremental intervention‐only implementation cost ranged from $88 to $215. Conclusions: The current findings indicate that non‐nurse PN can increase colonoscopy completion, and this can be achieved at a minimal incremental cost for an insured population at an urban academic medical center. Abstract : This report examines the cost effectiveness of a new patient navigation program implemented at the University of Chicago Medical Center to increase colonoscopy‐based colorectal cancer screening. The findings indicate that, for a screen‐eligible population, patient navigation can increase colonoscopy completion and reduce no‐show rates with low incremental costs to support the process.